TINJAUAN ATAS PERMASALAHAN PENEGAKAN HUKUM DAN PEMENUHAN HAK DALAM KONTEKS UNIVERSALIME DAN RELATIVISME HAK ASASI MANUSIA DI INDONESIA - Ridwan Arifin; Rasdi Rasdi; Riska Alkadri (Faculty of Law, University of Muhammadiyah Malang, 2018)
The four principles of freedom (four freedoms) include freedom of speech and expression, freedom of religion and belief, freedom from want, and freedom from fear, are basic principles recognized by countries and translated into many more specific forms of human rights fulfillment human. The fulfillment and protection of human rights is one indicator of the progress of a country. The scope of fulfilling human rights that covers a very broad field, from education, health, to law enforcement, is a challenge. The UN Security Council 2017 Universal Periodical Review (UPR) session provides recommendations for strengthening human rights in Indonesia, including the ratification of international human rights instruments, the continued cooperation of UN human rights, the abolition of the death penalty, matters related to sexual orientation and efforts to protect tolerance and diversity. The Commission for Missing Persons and Victims of Violence (Kontras) 2017 records 84 cases of violence and human rights violations that occurred. The issue of interpreting different human rights standards is one of the causes of this high problem in Indonesia. Many different interpretations are caused by the running of different political systems of state administration, causing the implementation of human rights fulfillment to be different. This paper looks at and compares the practices of human rights enforcement covering the four principles of freedom in Indonesia. This paper will compare the implementation of human rights standards and norms in national domestic practices based on international human rights principles and norms.